2017
DOI: 10.1080/13880209.2017.1387575
|View full text |Cite
|
Sign up to set email alerts
|

Rutin ameliorates oxidative stress and preserves hepatic and renal functions following exposure to cadmium and ethanol

Abstract: Context: Rutin (RUT) is an antioxidant flavonoid with well-known metal chelating potentials.Objective: This study was designed to evaluate the protective effects of RUT against cadmium (Cd) + ethanol (EtOH)-induced hepatic and renal toxicity in rats.Materials and methods: Wistar rats were treated with Cd (50 mg/kg) alone or in combination with EtOH (5 mg/kg) and RUT (25, 50 and 100 mg/kg) for 15 days. After treatment, the liver, kidney and serum were removed for biochemical assays by spectrophotometric methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Another finding parallel to this damage is a decrease in the body weight of animals and a significant increase in liver weight and liver weight/body weight ratio. Comparing current studies with previous studies on cadmium exposure; oxidative stress parameters (Abarikwu, Njoku, Lawrence, Charles, & Ikewuchi, ; Dkhil et al, ; Eşrefoglu et al, ; Jurczuk et al, ; Karaca and Eraslan, ; Koyu et al, ; Layachi and Kechrid, ; Xu et al, ; Zhang et al, ), some biochemical parameters (Abarikwu et al, ; Layachi & Kechrid, ; Pari & Murugavel, ; Pari & Shagirtha, ; Zhang et al, ), liver histopathology (Andjelkovic et al, ; Koyu et al, ; Olisekodiaka, Igbeneghu, Onuegbu, Oduru, & Lawal, ; Xu et al, ) and, in terms of body weight and liver weight (Layachi & Kechrid, ) have similarities.…”
Section: Discussionsupporting
confidence: 62%
“…Another finding parallel to this damage is a decrease in the body weight of animals and a significant increase in liver weight and liver weight/body weight ratio. Comparing current studies with previous studies on cadmium exposure; oxidative stress parameters (Abarikwu, Njoku, Lawrence, Charles, & Ikewuchi, ; Dkhil et al, ; Eşrefoglu et al, ; Jurczuk et al, ; Karaca and Eraslan, ; Koyu et al, ; Layachi and Kechrid, ; Xu et al, ; Zhang et al, ), some biochemical parameters (Abarikwu et al, ; Layachi & Kechrid, ; Pari & Murugavel, ; Pari & Shagirtha, ; Zhang et al, ), liver histopathology (Andjelkovic et al, ; Koyu et al, ; Olisekodiaka, Igbeneghu, Onuegbu, Oduru, & Lawal, ; Xu et al, ) and, in terms of body weight and liver weight (Layachi & Kechrid, ) have similarities.…”
Section: Discussionsupporting
confidence: 62%
“…It should be emphasized that although at the low-level exposure to Cd oxidative stress was noted after 10 months, unfavorable changes of some parameters of the oxidative/antioxidative barrier were recorded already after 3 months of the intoxication. Taking into account the fact that morphological changes in hepatocytes, including oxidative damage to the cellular and intracellular membranes, result in disorders in the proper function of the liver [23,24,25,41,44,45,46]; based on the findings of the present study it can be concluded that low chronic exposure to Cd may also impair the function of this organ. The pathological changes in the morphological picture of the liver described by us are similar to these observed by other authors due to repeated intoxication with Cd [23,24,40,41,44,45].…”
Section: Discussionmentioning
confidence: 58%
“…Increased body weights of rats in all groups, during the 60 days exposure to TO diets, indicates the absence of general toxicity (Abarikwu, Olufemi, et al., ). The nonsignificant decrease in relative and absolute testes weights of rats consuming 10% and 15% TO‐supplemented diets could be due to mild aberrant morphology (Abarikwu, Njoku, Lawrence, Charles, & Ikewuchi, ) and also indicates that boiled seeds of TO are toxic to the interstitial tissue and seminiferous tubules (Adisa et al., ; Kassem et al., ). Increased abnormal sperm morphology and reduced epididymal sperm number were also observed in rats administered TO diets.…”
Section: Discussionmentioning
confidence: 99%
“…The elevation and/or reduction in antioxidant defence systems accompanied by a concomitant increase in MDA concentration highlights the induction of oxidative stress (Abarikwu, Njoku, et al., ; Imamoğlu, Bülbül, Kaklikkaya, & Sarihan, ). More so, the increase in the activities or levels of antioxidant defence in experimental models is seen as an adaptive response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%